Clinical outcomes of different therapeutic modalities for rectal gastrointestinal stromal tumor: Summary of 14-year clinical experience in a single center. (May 2020) - Shu, P.; Sun, X.F.; Fang, Y.; Gao, X.D.; Hou, Y.Y.; Shen, K.T.; Qin, J.; Sun, Y.H.; Qin, X.Y.; Xue, A.W.; Fu, M.
Abstract: Objective: The optimal treatment for gastrointestinal stromal tumor (GIST) of the rectum is controversial due to the extremely low incidence of the disease. The aim of the present study was to compare the clinical outcomes of different treatment modalities for rectal GIST by reviewing the 14-year experience in our center. Method: Medical records of rectal GIST patients who received surgical treatment in our center between January 2004 to December 2017 were reviewed retrospectively. Overall survival (OS) and recurrence-free survival (RFS) were used as the observation endpoints. Results: Included in this study were 71 GIST patients, including 42 patients who underwent local excision (LE) and 29 patients who underwent segmental resection (SR). There were differences in tumor size (P = 0.001) and malignant risk grade (P = 0.007). The LE approach achieved a lower rate of R0 resection than SR (29/42 vs.27/29, P = 0.015) and shorter hospital stay (P = 0.004). Preoperative imatinib mesylate (IM) therapy improved the rate of sphincter-sparing surgery for patients with tumors in the very low segment of the rectum (P = 0.012) and offered better R0 resection margins (P = 0.027). Multivariate analysis showed that the resection margin status (P = 0.014), risk stratification (P = 0.001) and IM therapy (P = 0.042) were independent factors affecting RFS of rectal GIST patients but not the surgical modalities (LE vs. SR, P = 0.802). Multivariate analysis showed no significant impact of these variables on OS. Conclusion: Selection of surgical modalities has no significant impact on the prognosis. Local excision is the preferred surgical modality for resectable rectal GIST by virtue of less injury and shorter hospital stay. IM therapy has proved to be associated with improved RFS for rectal GIST patients. Highlights: Selection of surgical modalities has no significant impact on the prognosis. Preoperative treatment with Imatinib improves the rate of the sphincter-sparing procedure. The risk grade, resection margin status and Imatinib treatment are independent factors affecting recurrence-free survival.